2021
DOI: 10.2196/18286
|View full text |Cite
|
Sign up to set email alerts
|

Young People’s Use of Digital Health Technologies in the Global North: Narrative Review

Abstract: Background A diverse array of digital technologies are available to children and young people living in the Global North to monitor, manage, and promote their health and well-being. Objective This article provides a narrative literature review of the growing number of social research studies published over the past decade that investigate the types of digital technologies used by children and young people in the Global North, in addition to investigating which of these … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
84
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 89 publications
(70 reference statements)
6
84
0
7
Order By: Relevance
“…TikTok videos could thus contribute to this reduction in inequalities. To be efficient, the oral health education strategy must be implemented early in life and thus must target a young audience, especially children and adolescents [ 40 , 41 ]. The first line of defense against the apparition of oral diseases such as caries and periodontal diseases has traditionally been patient education, with a special emphasis on optimal oral hygiene [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…TikTok videos could thus contribute to this reduction in inequalities. To be efficient, the oral health education strategy must be implemented early in life and thus must target a young audience, especially children and adolescents [ 40 , 41 ]. The first line of defense against the apparition of oral diseases such as caries and periodontal diseases has traditionally been patient education, with a special emphasis on optimal oral hygiene [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, use of personal/individual Fitbit devices has been reported to decrease adolescence motivation and MVPA (Kerner et al, 2019 ). Previous research has also indicated that there could be negative health and well-being outcomes from self-tracking by encouraging obsessive monitoring behaviors and peer comparisons (Goodyear et al, 2019 ; Kerner et al, 2019 ; Lupton, 2021 ). Therefore, careful consideration should be given to the way in which these technologies are implemented.…”
Section: Discussionmentioning
confidence: 99%
“…As digital natives , today’s youth may find digital approaches to nutrition education more meaningful and impactful than the conventional approaches [ 17 ]. The internet, telehealth, gaming, social media, mobile apps, and wearable devices are few digital platforms that have been used to promote health among the youth, with varied impacts [ 18 ]. Before the COVID-19 pandemic, digital interventions were already rapidly developing as anonymous, accessible, and cost-effective interventions appealing to the youth [ 16 ].…”
Section: Introductionmentioning
confidence: 99%